Smartphones: Feasibility for real-time sports monitoring - McCarthy, M.W.; James, D.A.; Rowlands, D. D. (Procedia Engineering, 2013)
Sports monitoring technologies such as wireless sensor packages offer greater insight into the performance of athletes. The costs and complexities associated with these technologies can be prohibitive, particularly to sub-elite and amateur groups. Smartphones are a cheaper, more familiar technology with adequate capabilities for capturing many sports related activities. This paper shows the feasibility of smartphones for use in a real-time monitoring environment for sports applications. Capture of sports related activities is conducted using both internal and external sensors and the data used to identify key features of a cricket bowler delivery. The effects of distance, antenna orientation and body occlusion on signal strength are tested and show that real-time data can be reliably transmitted up to 100 meters. The power use of commonly used smartphone subsystems is used to calculate the minimum duration of a typical monitoring application and show that the lifetime is suitable for many sports. The benefits and challenges of using smartphones for these applications is also discussed, including those faced when utilising these devices across larger groups for real-time monitoring of teams.